2017
DOI: 10.1109/tsmc.2016.2563386
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students’ Engagement With Systems Thinking: Results of a Survey Study

Abstract: This paper describes the results obtained for the affective engagement of students with systems thinking. In prior work the authors have developed and validated a questionnaire instrument for measuring affective engagement of undergraduate engineering students with systems thinking. This paper presents results obtained when the questionnaire was used with undergraduate students. Two surveys with different versions of the questionnaire, one using positive grammar questions only and the other using a mix of posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…A project-based learning approach is considered an appropriate teaching and learning approach to enable students' experiential learning and to provide the motivational context that builds affective learning. This position is supported by the finding of a previous study [8] that showed an experiential learning environment supports the development of students' engagement with ST practice, the affective domain. With a project-based learning approach, over a semester students can TE-2018-000344 7 assume the role of a systems engineer and become involved in the development of a complex systems project, for example the design of a five-star hotel, a water desalination plant, or an amusement or theme park.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…A project-based learning approach is considered an appropriate teaching and learning approach to enable students' experiential learning and to provide the motivational context that builds affective learning. This position is supported by the finding of a previous study [8] that showed an experiential learning environment supports the development of students' engagement with ST practice, the affective domain. With a project-based learning approach, over a semester students can TE-2018-000344 7 assume the role of a systems engineer and become involved in the development of a complex systems project, for example the design of a five-star hotel, a water desalination plant, or an amusement or theme park.…”
Section: Discussionsupporting
confidence: 63%
“…The questionnaire uses a seven-point Likert scale for each item. The scale reflected theoretical, methodological and practical aspects of ST [8], [19].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations